Inadvertent injection of potassium chloride instead of sodium chloride during treatment of chronic low back ache with epidural injection leading to paraplegia - Rahul Ranjan; Naiyer Asif; Sohail Ahmad; Syed Ifthekar (Journal of Craniovertebral Junction and Spine, 2016)
Epidural injection of steroid is given for back pain resistant to other conservative management. Normal saline (NS) is used as diluent in 80 mg methylprednisolone and a local anesthetic. Due to a similar looking ampoule of NS and potassium chloride (KCl), there is a probability of accidental use of KCl instead of NS. We present a case of a 50 year old male patient having low back ache refractory to other conservative treatments. Epidural injection of steroid was given, but accidently KCl was mixed with methylprednisolone instead of NS. He developed severe cramps in the lower limbs, pruritus, and sweating, and finally paraplegia. Electrocardiography and blood showed features suggestive of hyperkalemia. He was given calcium gluconate and potassium chelating agent along with supportive measures. The patient recovered within 8 h. It is concluded that calcium gluconate and potassium chelating agent can be used if accidentally KCl is injected in epidural space.